Performance of the Celera Diagnostics ViroSeq HIV-1 Genotyping System for Sequence-Based Analysis of Diverse Human Immunodeficiency Virus Type 1 Strains - Eshleman, Susan H. (American Society for Microbiology, 2004)
The Celera Diagnostics ViroSeq HIV-1 Genotyping System is a Food and Drug Administration-cleared, integrated system for sequence-based analysis of drug resistance mutations in subtype B human immunodeficiency virus type 1 (HIV-1) protease and reverse transcriptase (RT). We evaluated the performance of this system for the analysis of diverse HIV-1 strains. Plasma samples were obtained from 126 individuals from Uganda, Cameroon, South Africa, Argentina, Brazil, and Thailand with viral loads ranging from 2.92 to >6.0 log(10) copies/ml. HIV-1 genotyping was performed with the ViroSeq system. HIV-1 subtyping was performed by using phylogenetic methods. PCR products suitable for sequencing were obtained for 125 (99%) of the 126 samples. Genotypes including protease (amino acids 1 to 99) and RT (amino acids 1 to 321) were obtained for 124 (98%) of the samples. Full bidirectional sequence data were obtained for 95 of those samples. The sequences were categorized into the following subtypes: A1/A2 (16 samples), B (12 samples), C (13 samples), D (11 samples), CRF01_AE (9 samples), F/F2 (9 samples), G (7 samples), CRF02_AG (32 samples), H (1 sample), and intersubtype recombinant (14 samples). The performances of the individual sequencing primers were examined. Genotyping of duplicate samples in a second laboratory was successful for 124 of the 126 samples. The identity level for the sequence data from two laboratories ranged from 98 to 100% (median, 99.8%). The ViroSeq system performs well for the analysis of plasma samples with diverse non-B subtypes. The availability of this genotyping system should facilitate studies of HIV-1 drug resistance in non-subtype B strains of HIV-1.